Sharing the Power of the ARIS BI Toolkit: The Development and Evolution of a Consulting Protocol for BI Professionals - Tiffany Willoughby; Leah Bug (The University of Alabama, 2024)
The ARIS Broader Impacts (BI) Toolkit Consultation Protocol (BITCoP) was designed to help BI professionals deliver foundational knowledge and resources to support higher education staff and faculty in developing BI plans for their NSF proposals. Beyond the scope of the National Science Foundation's Proposal and Award Policies and Procedures Guide, BITCoP was designed to address key terminology, valuable resources, and the usefulness of the ARIS BI Toolkit. Goals of the BITCoP include to give BI professionals nationwide a mechanism for delivering consultations that result in robust BI plans and gain insight into the evolving needs of the research community.